Hubungan Antara BMI dan VO2max terhadap Keterampilan Sepakbola Atlet Akademi Sepakbola Safin Pati - Muhammad Alkayyis; Purwono Sidik Permono (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aims to analyse the relationship between body mass index and cardiovascular endurance on basic football skills in 17-year-old athletes at the Safin Pati Football School. Materials and methods. This study used a quantitative approach with a correlational method. The study was conducted at the Safin Pati Football School, Pati Regency, Central Java. The research sample consisted of 18 active athletes who were members of the 2025 Pati Regency football team, aged 17 years. The research instruments included body mass index measurements, cardiovascular endurance tests using the bleep test, and basic football skill tests covering heading, passing, dribbling, and speed shooting. Data analysis was performed using Pearson's correlation test with the assistance of SPSS version 27 software. Results. The results showed that both body mass index and cardiovascular endurance had a significant relationship with football skills. Body mass index contributed effectively by 14.9%, while cardiovascular endurance contributed effectively by 0.6%. The combined contribution of both to football skills was 15.5%, while the rest was influenced by other factors that were not studied. The novelty of this study lies in its focus on Safin Pati Football School, a football school that specifically focuses on coaching athletes to prepare them for careers in professional football. Conclusion. Body mass index and cardiovascular endurance play a role in supporting basic football technical skills. These findings can serve as a basis for coaches to consider when designing physical training programmes and managing athletes' physical condition optimally.